Thinking radical democracy : the return to politics in post-war France - Breaugh, Martin, 1973-; Holman, Christopher, 1979-; Magnusson, Rachel, 1980-; Mazzocchi, Paul, 1979-; Penner, Devin, 1980- (University of Toronto Press, 2015)
Thinking Radical Democracy is an introduction to nine key political thinkers who contributed to the emergence of radical democratic thought in post-war French political theory.